(untitled) (Global Journal of Computer Science and Technology, 2025)
This paper analyzes the challenges of trunk stock management for field service operations and proposes improvement solutions Trunk stock the inventory carried by field service technicians poses unique management challenges due to its mobile nature and frequent transactions Manual reporting methods can lead to errors and delays resulting in stockouts overstocking or inaccurate costing The research proposes integrating mobile inventory scanning with cloud-based software to track inventory in real-time or near real-time Additionally the study explores the potential of the consignment process in SAP ERP for managing trunk stock A field study and SAP ERP pilot are outlined to test the proposed solutions The findings aim to provide insights for service organizations to enhance trunk stock management practices reduce errors and improve operational efficiency The paper concludes by discussing the implications and suggesting areas for further research including the application of emerging technologies like IoT sensors and blockchain